Wage dynamics in Denmark - Peter E. Storgaard (Danmarks Nationalbank, 2011)
Compared with the previous decades the rate of wage increase in Denmark has been subdued since the mid-1990s, given the pressure that gradually arose in the labour market. The paper describes changes in the labour market in recent years, including labour-market reforms and decentralisation of wage formation, and an empirical analysis of wage development in Denmark from 1975 to 2007 is performed. The results indicate that in the long term Danish wage development can be described by a real-wage curve. In the short term a wage equation with error correction towards this real-wage curve seems to outperform a simple Phillips curve.
Keywords: 330; Arbeitsmarkt; Lohnverhandlungen; Dezentralisierung; Lohnniveau; Phillips-Kurve; Dänemark